If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=e+6
We move all terms to the left:
3-(e+6)=0
We get rid of parentheses
-e-6+3=0
We add all the numbers together, and all the variables
-1e-3=0
We move all terms containing e to the left, all other terms to the right
-e=3
e=3/-1
e=-3
| 26=-2(-2x+3) | | 3(d-2)=84 | | 2x-(-8)=4 | | 2+3(x-8)=26 | | 2(-6x-5)=26 | | 3x+14+2x+20=6x+17 | | -3(2h-7)=45 | | 40x+(10x*1.5)=2600 | | 1/3x3=72 | | 33=8+5(v-3) | | 76=-4(2f-7) | | 76=-4(2f-7 | | y-1.12=9.5 | | 4x+2+30=8+6× | | 1.5x-5=0.8x | | 2(-6n-5)=98 | | g/8-5=1.5 | | 9x^2-18x+9=16 | | g/8-5=1/1/2 | | 4(.75x-1)=7x-20 | | -7x+4-(5x-7)=7x-9 | | 9x^2-18+9=16 | | 3m-2÷5=25 | | 2x^2+x-126=0 | | 95+60+x=180 | | -7c-12c-7c+c=16 | | n(7n+8)=–10 | | (6v^2-3v-2)=(v^2-7v+5) | | 5x-(-7)=-13 | | 16x^2-84x-190=0 | | 11t+2t-7t+4t-6t=16 | | z−z+1=z+1 |